Substance use among students in Thailand - Pimpisa Chomsri (2018)
© 2018 Taylor & Francis This study explored substance use prevalence, level of risk, and associated factors, especially related to binge drinking. A cross-sectional study was conducted among 306 students using questionnaires and the Alcohol, Smoking, and Substance Involvement Screening Test—Youth screening tool. The associations between binge drinking and risk factors were analyzed by generalized linear models. Our results showed current prevalence rates of alcohol, tobacco, and drugs use were 56.9%, 22.9%, and 2.3%, respectively. Multivariate analyses showed that being a binge drinker was significantly associated with low self-efficacy, high sensation seeking, moderate to high smoking risk, and low grade point average.